Role of streptokinase in management of retained hemothorax: a multicentric study - Varma, Ankur; Narain, Ravikant; Deshmukh, Parag; Rathore, Himmat; Datta, S. G. S.; Varma, Aditi V.; Sharma, Pawan; Joseph, Jebin (International Surgery Journal, 2020)
Background: Enzymatic debridement of the pleural cavity for retained haemothorax is a frequently overlooked option. Methods: A retrospective, multicentre study was carried out using intrapleural streptokinase was carried out in 15 patients with retained or clotted haemothorax. Results: Thirteen of fifteen patients (86%) with retained pleural collections underwent successful enzymatic debridement and tube drainage with streptokinase injections in our study. The average increase in chest tube output following streptokinase injections was 160%. No significant adverse reactions occurred. Two patients required thoracotomy when streptokinase therapy failed. No deaths were reported in the study. Conclusions: Intrapleural streptokinase is a safe, effective means of removing retained proteinaceous collections in the pleural space. It is a useful adjunct to chest tube drainage and may obviate the need for more invasive procedures.